Leaderless Jihad : Terror Networks in the Twenty-First Century - Sageman, Marc; Published in Collaboration with: University of Pennsylvania Press (New Delhi Manas Publications, 2009)
"In Leaderless Jihad, Marc Sageman documents how Islamist terror networks are evolving into more fluid, independent, and unpredictable entities than their more structured forerunners that carried out the atrocities of 9/11. These "homegrown" wannabes form a scattered global network, a leaderless jihad. Although physically unconnected, they constitute a virtual yet violent social movement as their fluid membership drifts to Internet chat rooms that connect them and provide them with inspiration and guidance. As the threat has migrated from outside to inside Western countries, the challenge for governments lies in detecting and neutralizing these groups before they become violent." "Drawing on historical analogies, Sageman argues that jihadism is self-limiting in terms of both structural capability and appeal. Eventually, its followers will turn away from violence as a means of expressing their discontent. The book concludes with Sageman's recommendations for counterterrorism law enforcement efforts. Homeland security, he argues, is best accomplished through a strategy of bringing to Justice real terrorists, containing potential terrorists, and exercising restraint with respect to the Muslim community."
Include Bibliography, Notes and Index.
In the post-September 11 world, Al Qaeda is no longer the central organizing force that aids or authorizes terrorist attacks or recruits terrorists. It is now more a source of inspiration for terrorist acts carried out by independent local groups that have branded themselves with the Al Qaeda name. Building on his previous groundbreaking work on the Al Qaeda network, forensic psychiatrist Marc Sageman has greatly expanded his research to explain how Islamic terrorism emerges and operates in the twenty-first century. InLeaderless Jihad, Sageman rejects the views that place responsibility for terrorism on society or a flawed, predisposed individual. Instead, he argues, the individual, outside influence, and group dynamics come together in a four-step process through which Muslim youth become radicalized. First, traumatic events either experienced personally or learned about indirectly spark moral outrage. Individuals interpret this outrage through a specific ideology, more felt and understood than based on doctrine. Usually in a chat room or other Internet-based venues, adherents share this moral outrage, which resonates with the personal experiences of others. The outrage is acted on by a group, either online or offline.Leaderless Jihadoffers a ray of hope. Drawing on historical analogies, Sageman argues that the zeal of jihadism is self-terminating; eventually its followers will turn away from violence as a means of expressing their discontent. The book concludes with Sageman's recommendations for the application of his research to counterterrorism law enforcement efforts.
Keywords: Terrorism -- a